Attitudes of People Living with HIV/AIDS at Babcock University Teaching Hospital Regarding Factors Affecting Adherence to Antiretroviral Regimens - Okoroafor, Obeka, Maxwell; Olatunji, Muideen Babatunde; Oboh, Joy Isioma; Oluwaseyi, Aibinuomo Ayomide; Daramola, Kolawole Tunmise; Ajoke, Agboola Abimbola; O., Ayinde, Abayomi (American Journal of Biomedicine and Pharmacy, 2024)
Background: Antiretroviral Therapy (ART) adherence is a critical factor in managing HIV/AIDS, significantly impacting patient health outcomes and the broader goal of reducing HIV transmission. Despite the availability of ART, adherence remains a challenge due to various patient-level and health institution-level factors. This study assesses the attitudes of People Living with HIV/AIDS (PLWHA) at Babcock University Teaching Hospital (BUTH), Nigeria, towards factors affecting adherence to ART regimens. Objectives: The primary aim is to evaluate the attitudes of PLWHA at BUTH regarding factors influencing adherence to ART. The specific objectives include: 1) Assessing the attitude towards ART among PLWHA at BUTH, 2) Identifying patient-level factors contributing to ART adherence, and 3) Evaluating health institution-level factors affecting ART adherence. Methods: This cross-sectional descriptive study was conducted at BUTH, Babcock University Teaching Hospital is located in Ilishan Remo, Ogun State, Nigeria. The hospital serves a diverse population, including men, women, and children from various parts of the country. Data were collected from 105 respondents attending the HIV clinic, where ART is provided free of charge. A structured questionnaire was used to gather information on demographic characteristics, knowledge, attitudes, and factors influencing ART adherence. Data were analyzed using descriptive and inferential statistics, with chi-square tests employed to determine associations between variables at a significance level of p < 0.05. Results: The majority of respondents were aged 31-40 years (38%) and predominantly female (58.3%). A significant proportion of respondents (76.2%) were married, and most identified as Christians (80.9%). Educational attainment was high, with 76.2% having tertiary education. Most respondents (78%) were employed, and the majority fell within the middle-income range (50,001-100,000 Naira monthly). Awareness of ART benefits was generally high, with 57.1% recognizing that ART can extend life expectancy and 76.2% understanding its role in suppressing viral load. However, gaps in knowledge were evident, with 49% unable to recall the meaning of ART and 54.6% unaware that forgetfulness is a key factor in non-adherence. The negative attitude of healthcare workers was identified as a significant barrier to adherence, recognized by 28.6% of respondents. Statistical analysis revealed a significant relationship between the perception that ART suppresses viral load and the belief that income, education, and literacy affect adherence (chi-square = 25.610, p = 0.000). Additionally, a significant association was found between recognizing the benefits of ART adherence and the impact of healthcare worker attitudes (chi-square = 21.115, p = 0.002). Conclusion: The study highlights that while there is considerable awareness of the benefits of ART among PLWHA at BUTH, significant barriers to adherence persist, particularly related to socioeconomic factors, healthcare worker attitudes, and knowledge gaps. Addressing these issues through targeted interventions is essential for improving ART adherence and achieving better health outcomes. Recommendations: The study recommends implementing comprehensive educational programs to close knowledge gaps, addressing socioeconomic barriers through support systems, enhancing healthcare worker training to foster positive patient interactions, and simplifying treatment regimens to reduce the complexity of adherence. These measures are crucial for improving adherence rates among PLWHA and achieving long-term HIV management goals.